Mercury in Active‐Layer Tundra Soils of Alaska: Concentrations, Pools, Origins, and Spatial Distribution. Issue 7 (20th July 2018) - Olson, C.; Jiskra, M.; Biester, H.; Chow, J.; Obrist, D.
Abstract: Tundra soils serve as major sources of mercury (Hg) input to the Arctic Ocean via river runoff and coastal erosion; yet little information is available on tundra soil Hg concentrations, pool sizes, origins, and dynamics. We present a detailed investigation of Hg in the active layer (upper ~100 cm subject to seasonal thaw) of tundra soils across 11 sites in Alaska. Soil Hg concentrations in organic horizons (151 ± 7 μg/kg) were in the upper range of temperate soil organic horizons, and concentrations in mineral horizons (98 ± 6 μg/kg) were much higher than in temperate soils. Soil Hg concentrations declined from inland to coastal sites, in contrast to a hypothesized northward increase expected because of proximity to coastal atmospheric mercury depletion events. Principle component analyses and elemental ratios results show that exogenic sources dominated over geogenic sources—in A‐horizons (66 ± 4%) and mineral B‐horizons (51 ± 1%). 14 C age‐dating suggested recent origins of Hg in surface soils but showed that mineral soils (more than 7, 300 years old) must have accumulated atmospheric inputs across millennia leading to high soil concentrations and pools. We estimated a total Northern Hemisphere active‐layer tundra soil Hg pool of 184 Gg (range of 136 to 274 Gg), suggesting a globally important Hg storage pool. Tundra soils are subject to seasonal thaw and freeze dynamics, thereby providing large inputs to rivers, lakes, and the Arctic Ocean. Understanding processes that mobilize Hg from tundra soils will be critical to understanding future Arctic wildlife and human Hg exposures. Key Points: Active‐layer tundra soils are high in soil mercury (Hg) concentrations despite the tundra's remote location Tundra soil Hg is derived from both recent and long‐term atmospheric deposition that accumulated in deeper soils through many millennia Tundra Hg pools sizes are large (184 Gg), determined by depth of the active layer and mineral horizons, and form a large global pool of Hg